Radio Block Center Used in Heavy Haul Railway Intelligent Driving System - LI Qihe (Kongzhi Yu Xinxi Jishu)
Intelligent driving system is the development direction of heavy haul railway,automatic train protection (ATP) system to ensure the safety of train is the basis of intelligent driving system and radio block center (RBC) is the wayside ATP core equipment used in high speed railway. Different from the existing RBC, this paper proposes a new type of RBC which aims at heavy haul railway. Based on the characteristics of the heavy haul railway intelligent system, the RBC core functions such as radio communication, train location, movement authority, temporary speed restriction, etc. are improved. Wireless interface with LKJ is added, so the control command can be sent from wayside to LKJ instantly; LTE wireless network is used for onboard-wayside communication to replace GSM-R in order to adapt to the requirement of moving block which need higher frequency communication session; virtual balise technology based on Beidou GNSS is used for train location, which can save cost and avoid ambiguous train position; configuration function is used for switching between fixed block and moving block; temporary speed restriction command is issued based on the format of LKJ to adaption the custom of drivers;and a new function called shunting protection is added. The RBC has been successfully applied to Shenhua locomotive intelligent driving system, its vehicle control rate is more than 90% and the number of operated heavy haul railway trains is 5~6 more than normal, which helps improve the operation efficiency of Shenshuo heavy haul railway.